Advances in the Arms Race Between Silkworm and Baculovirus - Jiang, Liang; Goldsmith, Marian R.; Xia, Qingyou (Frontiers in Immunology, 2021)
Insects are the largest group of animals. Nearly all organisms, including insects, have viral pathogens. An important domesticated economic insect is the silkworm moth Bombyx mori. B. mori nucleopolyhedrovirus (BmNPV) is a typical baculovirus and a primary silkworm pathogen. It causes major economic losses in sericulture. Baculoviruses are used in biological pest control and as a bioreactor. Silkworm and baculovirus comprise a well-established model of insect–virus interactions. Several recent studies have focused on this model and provided novel insights into viral infections and host defence. Here, we focus on baculovirus invasion, silkworm immune response, baculovirus evasion of host immunity, and enhancement of antiviral efficacy. We also discuss major issues remaining and future directions of research on silkworm antiviral immunity. Elucidation of the interaction between silkworm and baculovirus furnishes a theoretical basis for targeted pest control, enhanced pathogen resistance in economically important insects, and bioreactor improvement.